Noise Analysis of Bus Transmission Shaft and Improvement of Vibration Performance - Zhu Zhao; Huang Jun; Zhang Haiyuan; Jiang Hui (Jixie chuandong)
Aiming at a medium bus driving speed at 60 to 80 km/h,it is found that the problem of vehicle overall noise level is too large and greater vibration of the floor. By using the analysis of noise figure and the vibration waterfall map data,the transmission shaft intermediate support bracket course resonance is confirmed.According to the theory of vibration isolation and finite element analysis,by reducing the stiffness of the intermediate support rubber and increasing the natural frequency of the intermediate support bracket,the vehicle resonance phenomenon is greatly reduced and the vehicle noise is reduced by 4 dB（A）. This method has important reference significance in solving the noise of transmission shaft,structural optimization design and test verification.